2007
DOI: 10.1016/j.jembe.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrients, salinity, pH and light:dark cycle on the production of reactive oxygen species in the alga Chattonella marina

Abstract: Experiments were carried out to investigate the effects of nutrients, salinity, pH and light:dark cycle on growth rate and production of reactive oxygen species (ROS) by Chattonella marina, a harmful algal bloom (HAB) species that often causes fish kills. Different nitrogen forms (organic-N and inorganic-N), N:P ratios, light:dark cycles and salinity significantly influenced algal growth, but not ROS production.However, iron concentration and pH significantly affected both growth and ROS production in C. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 48 publications
4
50
2
1
Order By: Relevance
“…Although various studies have shown the individual importance of viral lysis, protozoan grazing, and endogenous and exogenous ROS in E. coli removal (Curtis et al, 1992;Bomo et al, 2004;Grobe et al, 2006;Liu et al, 2007;Kadir and Nelson, 2014), this is the first study, to our knowledge, to indicate the importance and interactions of all of these mechanisms for E. coli removal. Further, our approach enabled us to identify that the majority of the E. coli removal is due to top-down trophic interactions, such as protozoan grazing by M. brevicollis and T. spp and viral lysis by E. phages.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Although various studies have shown the individual importance of viral lysis, protozoan grazing, and endogenous and exogenous ROS in E. coli removal (Curtis et al, 1992;Bomo et al, 2004;Grobe et al, 2006;Liu et al, 2007;Kadir and Nelson, 2014), this is the first study, to our knowledge, to indicate the importance and interactions of all of these mechanisms for E. coli removal. Further, our approach enabled us to identify that the majority of the E. coli removal is due to top-down trophic interactions, such as protozoan grazing by M. brevicollis and T. spp and viral lysis by E. phages.…”
Section: Resultsmentioning
confidence: 78%
“…This is likely to have amplified changes in the carbonate-bicarbonate equilibrium induced by algal respiration, which has been shown to induce elevated growth rates and fruiting body formation in Sordaria spp (Elleuche and Pöggeler, 2010). This, in turn, results in further elevated CO 2 levels due to fungal respiration causing an additional imbalance in the carbonate-bicarbonate equilibrium and inducing a knock-on effect to the water pH, which has been shown to induce elevated algal ROS production (Liu et al, 2007). Such an association helps to explain the apparent mutualistic relationship displayed by fungi and algae during E. coli removal (Figure 6).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations